1534 A rare operation: resection of a complex malignant peripheral nerve sheath tumour deemed inoperable by a national centre. (12th October 2021) - Chowdhury, M. R; Goel, A; Sinha, P; Chave-Cox, R; Pal, D
Abstract: We present this rare case which was led by spinal surgeons at Leeds after being deemed not suitable for operative input by a national centre. A 54-year-old lady who presented with 2-month history of worsening left flank pain on a background of four years. She was otherwise fit and well. CT confirmed aggressive left-sided paraspinal tumour with epidural encroachment, extending from T8 to T10 vertebral levels. Its deep surface was well-defined and extending superficially through the chest wall with destruction of ribs. The mass grew in size in course of days requiring urgent attention due to risk of cord compression. Biopsy proved high grade MPNST. Malignant peripheral nerve sheath tumor (MPNST) is a rare type of sarcoma, 5-10% of sarcoma cases. MPNST is most common in young adults and middle-aged adults. About 25% to 50% of people with MPNST have NF1. 8% to 13% of people with NF1 will get MPNST in their lifetime. An MDT approach involving spinal, thoracic, vascular and plastic surgeons opined it requiring extensive surgery due to its complexity. It was performed in stages – embolisation then aortic stent placement followed by final resection of the tumour with chest well reconstruction using an LD flap. A multidisciplinary and multispecialty approach has led to a positive prognosis for this patient who is on the road to recovery.